2012
DOI: 10.1002/app.38722
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fire behavior of rigid polyurethane foam by intumescent flame retardants

Abstract: Using expandable graphite (EG) and ammonium polyphosphate (APP) as flame retardants, we prepared two series of polyisocyanurate-polyurethane (PIR-PUR) foams (i.e., EG foams filled with different amounts of EG alone and APEG foams containing different amounts of expanded EG and APP) and evaluated the effect of the additives on the physical-mechanical property, fire behavior and thermal stability of the foams based on compressive strength test, limiting oxygen index (LOI), cone calorimeter test, thermogravimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 17 publications
1
57
0
Order By: Relevance
“…As it was already well known, the presence of fairly high content of EG led to a decrease of the compression strength of the foams with respect to unfilled one. Since the amount and size of the different EGs used were the same for all the foams tested, the decrease of compression strength is very similar, that is the worsening of mechanical properties is related to EG size only.…”
Section: Resultsmentioning
confidence: 57%
“…As it was already well known, the presence of fairly high content of EG led to a decrease of the compression strength of the foams with respect to unfilled one. Since the amount and size of the different EGs used were the same for all the foams tested, the decrease of compression strength is very similar, that is the worsening of mechanical properties is related to EG size only.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, to improve the LOI value, vertical combustion UL-94 level and suppress the existed "popcorn effect" simultaneously, APP was added together in view of the reported synergistic effect between the two retardants. 35,36 LOI and UL-94 rating tests, thermal gravimetric and differential thermal gravimetric (TG/DTG) analyses were performed to investigate the flame retarded performance and the thermal stability. Electron microscope was applied to observe the residual char morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the influence of the EG content affected on flame retardant has been surveyed by Bian et al, and it revealed higher foam density and larger EG proportion were in favor of better flame retardancy. Hu et al and Meng et al also have systematically discussed the effect of EG on the flame retardancy and mechanical properties of RPUF, and they concluded that with the increasing of EG content, the flame retardancy would be improved, while the mechanical properties would be affected compared with original RPUF (Ref. RPUF).…”
Section: Introductionmentioning
confidence: 99%